Improved bandwidth of a 2 THz hot-electron bolometer heterodyne mixer fabricated on sapphire with a GaN buffer layer. (21st May 2019) - Antipov, S; Trifonov, A; Krause, S; Meledin, D; Kaurova, N; Rudzinski, M; Desmaris, V; Belitsky, V; Goltsman, G
Abstract: We report on the signal-to-noise and gain bandwidth of a niobium nitride (NbN) hot-electron bolometer (HEB) mixer at 2 THz fabricated on a sapphire substrate with a GaN buffer layer. Two mixers with different DC properties and geometrical dimensions were studied and they demonstrated very close bandwidth performance. The signal-to-noise bandwidth is increased to 8 GHz in comparison to the previous results, obtained without a buffer-layer. The data were taken in a quasi-optical system with the use of the signal-to-noise method, which is close to the signal levels used in actual astrophysical observations. We find an increase of the gain bandwidth to 5 GHz. The results indicate that prior results obtained on a substrate of crystalline GaN can also be obtained on a conventional sapphire substrate with a few micron MOCVD-deposited GaN buffer-layer.